2015
DOI: 10.1111/jace.13941
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Electrical Properties of Nonstoichiometric 0.94(Na0.5Bi0.5+x)TiO3–0.06BaTiO3Lead‐Free Ceramics

Abstract: 0.94(Na0.5Bi0.5+x)TiO3–0.06BaTiO3 (x = −0.04, 0, 0.02; named NB0.46T‐6BT, NB0.50T‐6BT, NB0.52T‐6BT, respectively) lead‐free piezoelectric ceramics were prepared via the solid‐state reaction method. Effects of Bi3+ nonstoichiometry on microstructure, dielectric, ferroelectric, and piezoelectric properties were studied. All ceramics show typical X‐ray diffraction peaks of ABO3 perovskite structure. The lattice parameters increase with the increase in the Bi3+ content. The electron probe microanalysis demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…The phenomenon has been previously attributed to the presence of increased oxygen vacancy concentration in literature. Higher oxygen vacancy concentration is expected to impact the grain boundary migration energy which leads to enhanced grain growth . The insets in Figure C,D represent backscattered electron images of the 4 mol% Fe‐doped compositions with highlighted secondary phases.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon has been previously attributed to the presence of increased oxygen vacancy concentration in literature. Higher oxygen vacancy concentration is expected to impact the grain boundary migration energy which leads to enhanced grain growth . The insets in Figure C,D represent backscattered electron images of the 4 mol% Fe‐doped compositions with highlighted secondary phases.…”
Section: Resultsmentioning
confidence: 99%
“…All samples, except x = 0.475, are considerably dense. With a decrease in x , the grain size of the ceramics gradually increases from about 0.5 to 3 μm, which can be attributed to the involvement of defects created by the bismuth volatility and the substitution of Bi 3+ with Na + . The overall reaction can be described using Kröger‐Vink notation,2BiBix+3normalOOx2VBi+3VO+Bi2normalO3false(normalgfalse)Na2Ofalse⟶Bi2O32NaBi+2VO+OOx…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that highly polarizable lone pair electrons of the Bi 3+ play an exceptionally important role in the dielectric and conduction. Excessive Bi 3+ suppressed the frequency dispersion and the conduction current in BNT and BNT‐based ceramics, and led to a pinched hysteresis loop because of the presence of the non‐ferroelectric state with antiparallel atomic shifts between Bi(Na) and Ti cations along the fourfold axis [001] . However, Bi 3+ deficiency enhanced the conductivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al reported that the nonstoichiometric quantities of Na and Bi exerted different effects on the macroscopic properties of BNT ceramics, eg, piezoelectric coefficient ( d 33 ) and depolarization temperature ( T d ). It was reported that, in the case of the BNT–0.06BT ceramics, the T d increased with an excess or deficient quantity of Bi 3+ , whereas nonstoichiometric quantities of Ti had an inverse reduction effect on T d . It is well known that during fabrication, the volatilization of Na 2 O and Bi 2 O 3 can produce positively charged oxygen vacancies that are vitally important to the ceramic's piezoelectric properties, due to high carrier mobilities .…”
Section: Introductionmentioning
confidence: 99%